Composition-tuned MAPbBr3 nanoparticles with addition of Cs+ cations for improved photoluminescence. Issue 39 (8th July 2021) - Dintakurti, Sai S. H.; Vashishtha, Parth; Giovanni, David; Fang, Yanan; Foo, Norton; Shen, Zexiang; Guet, Claude; Sum, Tze Chien; White, Tim
Abstract : Structural and optical properties of MA x Cs1− x PbBr3 mixed cation colloidal nanoparticles with 13 mol% Cs composition exhibiting the longest charge carrier lifetime and enhancement in radiative pathways. Abstract : Hybrid organic–inorganic lead halide perovskite nanoparticles are promising candidates for optoelectronic applications. This investigation describes the structural and optical properties of MA x Cs1− x PbBr3 mixed cation colloidal nanoparticles spanning the complete compositional range of Cs substitution. A monotonic progression in the cubic lattice parameter ( a ) with changes in the Cs + content confirmed the formation of mixed cation materials. More importantly, time-resolved photoluminescence (TRPL) revealed the optimized 13 mol% Cs nanoparticle composition exhibits the longest charge carrier lifetime and enhancement in radiative pathways. This sample also showed the highest photoluminescence quantum yield (PLQY) of ∼88% and displays ∼100% improvement in the PLQY of pure MAPbBr3 and CsPbBr3 . Prototype LEDs fabricated from MA0.87 Cs0.13 PbBr3 were demonstrated.